2014
DOI: 10.1007/s12088-014-0459-7
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Di- Through Hepta-Chlorobiphenyls in Clophen Oil Using Microorganisms Isolated from Long Term PCBs Contaminated Soil

Abstract: Present work describes microbial degradation of selected polychlorinated biphenyls (PCBs) congeners in Clophen oil which is used as transformer oil and contains high concentration of PCBs. Indigenous PCBs degrading bacteria were isolated from Clophen oil contaminated soil using enrichment culture technique. A 15 days study was carried out to assess the biodegradation potential of two bacterial cultures and their consortium for Clophen oil with a final PCBs concentration of 100 mg kg(-1). The degradation capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…PCBs are a family of man-made persistent organic chemicals that consist of a biphenyl skeleton where 1–10 hydrogen atoms are substituted by chlorine giving rise to up to 209 congeners. PCBs have been widely manufactured because of their chemical and physical properties ( National Research Council, 1979 ) and a significant amount of PCBs has been released into the environment ( Pieper, 2005 ; Sharma et al, 2014 ). The relative volatility of PCBs contributes to their spread throughout the globe ( Gomes et al, 2013 ) where they bioaccumulate and biomagnify in the food web ( Turrio-Baldassarri et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…PCBs are a family of man-made persistent organic chemicals that consist of a biphenyl skeleton where 1–10 hydrogen atoms are substituted by chlorine giving rise to up to 209 congeners. PCBs have been widely manufactured because of their chemical and physical properties ( National Research Council, 1979 ) and a significant amount of PCBs has been released into the environment ( Pieper, 2005 ; Sharma et al, 2014 ). The relative volatility of PCBs contributes to their spread throughout the globe ( Gomes et al, 2013 ) where they bioaccumulate and biomagnify in the food web ( Turrio-Baldassarri et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that between 1920 and early 1980s approximately 1.5 million tons of PCBs were manufactured throughout the globe and as a result of which a significant amount of PCBs has been released in the environment (Piper 2005; Sharma et al 2014). Due to their extensive use in past and lack of appropriate disposal technologies, PCBs and their congeners have attained ubiquitous distribution from the Arctic to the Antarctic.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are developed to manage or remediate these pollutants which include physical, chemical, and biological methods. Biological methods have an advantage over physical and chemical methods being cost incurred and environment friendly but have limitations with respect to effi ciency Sharma et al 2014 ). Soil microfl ora is able to degrade most of the organic contaminants, whereas metals need immobilization or physical removal.…”
Section: Introductionmentioning
confidence: 99%